2018
DOI: 10.1111/jdi.12904
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor alleviates hepatic insulin resistance and lipid accumulation in high‐fat diet‐fed mice

Abstract: HGF treatment can ameliorate hepatic insulin resistance and steatosis through regulation of lipid metabolism. These effects might occur through FXR-SHP axis dependent transcriptional activity. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
(33 reference statements)
0
19
2
Order By: Relevance
“…In 2008, the prevalence of diabetes mellitus in people living in Sandong Province who were aged ≥ 20 years was 9.9%, which was significantly higher than the average level in the whole country. For our study, we used a multi-stage stratified cluster sampling method to select participants, as described in detail in a previous study [ 27 ]. A total of 2481 diabetes patients registered in the NCDs management system in the sampling communities or villages were recruited to the survey, and 2183 diabetic patients for whom a complete dataset were available were included in the analysis, with a response rate of 87.99%.…”
Section: Methodsmentioning
confidence: 99%
“…In 2008, the prevalence of diabetes mellitus in people living in Sandong Province who were aged ≥ 20 years was 9.9%, which was significantly higher than the average level in the whole country. For our study, we used a multi-stage stratified cluster sampling method to select participants, as described in detail in a previous study [ 27 ]. A total of 2481 diabetes patients registered in the NCDs management system in the sampling communities or villages were recruited to the survey, and 2183 diabetic patients for whom a complete dataset were available were included in the analysis, with a response rate of 87.99%.…”
Section: Methodsmentioning
confidence: 99%
“…The adipokine visfatin that is released from the adipose tissue of obese individuals has also been shown to activate the pro-inflammatory STAT3 signaling pathway and NF-κB in the human liver cell line HepG2 and promote their insulin resistant state (108). Nevertheless, the hepatocyte growth factor (HGF) can alleviate the insulin resistance of hepatocytes and control their triglyceride and cholesterol contents (109).…”
Section: Livermentioning
confidence: 99%
“…Insulin is one of the most important hormones in the body. Its secretion has been precisely regulated by various substances such as nutrients, neurotransmitters, and hormones [ 39 , 40 , 41 ]. Research has shown that a key role for the brain is to act, via the sympathetic nervous system, in the rapid, highly coordinated, and reciprocal changes of insulin secretion and insulin sensitivity that preserve glucose homeostasis in a setting of cold exposure [ 42 ].…”
Section: Discussionmentioning
confidence: 99%